(untitled) (Journal of Rashid Latif Medical College, 2024)
Objective: Interns are frequently given teaching responsibilities in Pakistan. Interns are often recruited at the bottom of the teaching scale with little or no teaching experience and usually without any formal teacher training while pursuing undergraduate programs. Methodology: Assess the interns' level of teaching skill, so that if needed, appropriate action can be taken to raise the bar on instruction. This cross-sectional study was conducted by University of Faisalabad, from April to June 2023. Using Medical Education Teaching Readiness Questionnaire (METRQ) the knowledge, skill and attitude of the responders based on different experiences pertaining to medical teaching were accessed from fifty first-year dental interns approached for the questionnaire that was statistically evaluated in SPSS 21. Results: Forty (80%) of the interns considered that mastering the basics of teaching, for example planning "what to teach" was necessary, but they were not prepared to teach. For skills, 38 (76%) respondents said that viewing their lecturers was very helpful, while only 1 (2%) said receiving feedback on their own instruction was helpful. At graduation, most of the factors, ranked as traits of teaching—such as drive, excitement, and competence—began to depreciate. When some experience in teaching had been accumulated during the internship, similar qualities showed clearly higher ratings. Conclusion: In creating teacher-training programs or assessing the current state of those teaching in the health professions, METRQ can be a great tool to conduct needs assessments. Important for improving the quality of instruction and, thereby, the quality of education, are teacher training programs. Keywords: Aptitude, Cross sectional studies, Needs Assessment, Teacher training.